Simulation of Ti-6Al-7Nb alloy processing by equal-channel angular pressing (ECAP) using the finite element method - Conejo-Herrera, Mónica (2017)
In this work, the finite element method was used to analyze plastic deformation of a bar of Ti-6Al-7Nb with a squared cross section of 10 x 10 mm2 processed by equal-channel angular pressing (ECAP). Firstly, this process was simulated for different internal angles and internal and external radii of curvature of the channel, by a simplified 2D model. The influence of these parameters on the magnitude and homogeneity of the deformation, as well as on the applied load, was determined. From the 2D simulation results, optimum curvature radii for each internal angle was selected, based on a proposed design for the external dimensions and material of the ECAP processing die. Furthermore, it was determined by 3D simulation that the selected dimensions and material for the die are sufficient to withstand the high pressures involved in this process.